TRANSFORMING BUSINESS WITH MOBILE ENTERPRISE APPS (International Journal of Engineering and Computer Science, 2017)
Now a days mobile applications are much more accessible due to high-speed mobile networks; third and fourth generation networks provide more than enough bandwidth for personal and professional use, with email and mobile app stores almost ubiquitous on today’s devices. By 2013, over 80% of handsets sold in mature markets will be smartphones, with a text keyboard, 3G & 4G connectivity and multimedia features. Mobile applications have become an important strategic imperative to many leading enterprises. This research develops a conceptual multi-phase framework of mobile transformations by integrating the emerging literature on mobile business and enterprise transformation with best practice approaches employed in industry. While the potential value and impact of enterprise mobility is understood, only little is known about the transformational capabilities of mobile applications. The framework provides a basis for future mobile enterprise oriented studies, enhances our understanding of mobile application opportunities, and facilitates the development of appropriate mobility strategies.